Co-Morbidities and Characteristics of Adult Obese patients for Bariatric Surgery (Sleeve Gastrectomy) and their early Postoperative Complications - Seerat Fatima, Fakhra Fakhr, Aliya Naseer, Abdul Rehman, Mishal Shamsi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obesity is defined as an increase in body weight that is greater than 20 percent of an individual's ideal body weight; the weight is determined by certain factors, such as age, height, and gender. Obesity has become a real and serious health issue in the world. Obesity doesn’t come alone but associates with many other multiple diseases like type 2 diabetes mellitus (T2DM), hypertension (HTN) and many more. Sleeve gastrectomy is very beneficial as the surgical treatment of obesity but it also has some risks or complications. Complications may be early or could be long term. Aim: To determine comorbidities and characteristics of adult obese patients for bariatric surgery (Sleeve Gastrectomy) and their early postoperative complications Method: Data of 55 participants was taken age ranging from 18 to 60 years from record room of General Operation Theatre (GOT) department of Shalamar Hospital, Lahore. Other than age, weight and BMI of the participants, their comorbidities and complications were studied. Result: Average age of participants which was 41.345 years with standard deviation of8.097. Most patients were in category of 40 to 50 years age. There were 27 females and 28 males included in this study. 94.5% of the participants had limited physical work ability. Most common co-morbidity was arthritis (53%) then came snoring and hypertension (45% each) followed by sleep apnea (40%) and respiratory disease (36.4%), diabetes (34.5%), regurgitation (32.7%) and myocardial infarction at last with 7% frequency. Rate of post-operative complications was very low with 5.5% of bleeding and 3.6% of abscess and stomach leak both. Conclusion: This study concluded that co-morbidities increase with increasing weight and older age in a dose-response relationship. Also, respiratory disease and sleep apnea are more significant than other co-morbidities. Co-morbidities can be controlled with changing social structure and lifestyles. The problem can only get worse with time if not addressed by healthcare planners.